Human capital development issues in Malaysia - Mohd Rasdi, Roziah (Universiti Putra Malaysia Press, 2012)
Human Capital Development Issues in Malaysia is a book which provides comprehensive review of issues in Malaysia, covering significant human resources development concepts and practices in various contexts including education, youths, employability and the corporate world. It is an ideal reading for human resources development majors, practitioners, professionals and anybody who are interested to enhance their knowledge and understanding in this field. This book which builds on a foundation of research and theories addresses timely issues with pleasant writing style and realistic examples. Each chapter will benefit the readers due to the author’s insights and reflection on contemporary issues which are critical for the sustainability of human potentials and growth.